(untitled) (Eurasian Journal of Ecology, 2022)
Due to the annual increasing volumes of oil and petroleum products extraction and refining, the probability of ecosystem pollution with heavy hydrocarbons is increasing. At present, it is biological methods of soil purification that are the most promising methods from both an ecological and an economic point of view. The main mining regions are characterized by a hot climate and high salinity of the soil. It is known that the effectiveness of the use of destructive microorganisms largely depends on external environmental factors. Abiotic factors of ambient temperature and salinity of the initial soil directly affect the metabolic processes of bacteria. The purpose of this work was to study the ability of free and immobilized microorganisms on biological carriers to degrade oil under different temperature conditions and at different concentrations of mineral salts in the soil. It was found that with an increase in salinity, the degree of destruction decreases. However, with an increase in temperature, the level of destruction remained at the same level as at 5% NaCl. The degree of destruction is influenced by the temperature factor. The highest destruction result was shown by strains immobilized on rice husk. Whereas strains immobilized on buckwheat husks and free cells with increasing salinity and temperature show a low degree of purification. Immobilization of strains on solid organic carriers, protect from external influences and from fluctuations in ambient temperature. Key words: bioremediation, immobilization, temperature, salinity, rice husk, buckwheat husk, destructive microorganisms.